2019
DOI: 10.1136/lupus-2019-000352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D on serum markers of bone turnover in SLE in a randomised controlled trial

Abstract: ObjectiveBone health in SLE is adversely affected by vitamin D deficiency, inflammatory cytokines and glucocorticoid use. We hypothesised that vitamin D supplementation would increase markers of bone formation and decrease markers of bone resorption in SLE subjects.MethodsWe studied 43 vitamin D-deficient SLE subjects who participated in a 12-week randomised controlled trial of 2000–4000 IU/day vitamin D supplementation versus placebo. Subjects had inactive SLE (SLE Disease Activity Index ≤4) and were taking &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In patients with primary osteoporosis, its expression level tends to rise. Therefore, it is listed as an important indicator for the detection of clinical diagnosis and differential diagnosis of primary osteoporosis and written into the diagnostic guidelines (Tedeschi et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with primary osteoporosis, its expression level tends to rise. Therefore, it is listed as an important indicator for the detection of clinical diagnosis and differential diagnosis of primary osteoporosis and written into the diagnostic guidelines (Tedeschi et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that vitamin D plays a role in innate and specific immunity by regulating T lymphocytes; at the same time, studies have shown that vitamin D can not only affect the proliferation and maturation of T cells, but also reduce the expression of IL-17, promote the proliferation of Treg cells and enhance their immune tolerance [15,16] . Kevin et al [17] , Tedeschi et al [18] and Volt et al [19] detected that the downstream genes regulated by VDR are related to systemic lupus erythematosus and multiple sclerosis. Studies of Hau et al [20] , and Jeffery et al [21] showed that the therapeutic effect of 1.25(OH) 2 D 3 in rheumatoid arthritis and psoriasis was related to IL-17A.…”
Section: Discussionmentioning
confidence: 99%